2010
DOI: 10.1177/0333102410370870
|View full text |Cite
|
Sign up to set email alerts
|

CADASIL and migraine: A narrative review

Abstract: Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is caused by mutations in the NOTCH3 gene and is clinically characterized by recurrent stroke, cognitive decline, psychiatric disturbances and migraine. The prevalence of migraine in CADASIL is slightly higher than in the general population, and the proportion of migraine with aura is much higher. The pathophysiological mechanism that leads to increased aura prevalence in CADASIL is unknown. Possible mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 63 publications
2
54
1
Order By: Relevance
“…A higher prevalence of migraine in CADASIL was also reported in other studies, although not significantly [38]. A higher degree of cognitive impairment and cerebral atrophy was also noticed in men at the late stage of the disease [36,37].…”
Section: Discussionsupporting
confidence: 54%
“…A higher prevalence of migraine in CADASIL was also reported in other studies, although not significantly [38]. A higher degree of cognitive impairment and cerebral atrophy was also noticed in men at the late stage of the disease [36,37].…”
Section: Discussionsupporting
confidence: 54%
“…Five of our patients had migraine, two with and three without aura. Our series supports findings reporting that migraine without aura frequency is slightly higher in CADASIL patients compared with the general population 11 . Increased risk of ICH in CADASIL patients is based on case reports and it has not been proved with controlled studies.…”
supporting
confidence: 93%
“…When the results are pooled, the overall prevalence of migraine in all CADASIL studies is 38 % with a 95 % CI 33-42 %. The migraine prevalence in CADASIL was higher in females than in males, but this difference did not reach statistical significance [12]. The percentage of migraine with aura could only be inferred from two of the larger study [9,10], which showed that the majority (80-90 %) of migraneurs with CADASIL have migraine with aura.…”
Section: Genetic Vasculopathiesmentioning
confidence: 90%
“…The prevalence of migraine in CADASIL ranges from 14 to 72 % in European studies [9][10][11]. The four studies from Asian countries [12] found a low migraine prevalence of 5 %. When the results are pooled, the overall prevalence of migraine in all CADASIL studies is 38 % with a 95 % CI 33-42 %.…”
Section: Genetic Vasculopathiesmentioning
confidence: 99%